2010
DOI: 10.4238/vol9-2gmr776
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the dry bean polygalacturonase-inhibiting protein (PGIP) gene family during Sclerotinia sclerotiorum (Sclerotiniaceae) infection

Abstract: ABSTRACT. Polygalacturonase-inhibiting proteins are leucine-rich repeat proteins that inhibit fungal endopolygalacturonases. The interaction of polygalacturonase-inhibiting protein with endopolygalacturonases limits the destructive potential of endopolygalacturonases and may trigger plant defense responses induced by oligogalacturonides. We examined the expression of fungal pg and plant Pvpgip genes in bean (Phaseolus vulgaris) stems infected with Sclerotinia sclerotiorum to determine whether any of them are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
(46 reference statements)
3
7
0
Order By: Relevance
“…During infection of the P. vulgaris stem, the pattern of sspg expression was different from that observed in vitro: sspg1 and sspg3 were weakly expressed, sspg5 and sspg7 were highly expressed, and sspg6 displayed regulation during the later phases of infection (see Figure 5). We have previously reported similar observations (Oliveira et al, 2010). Furthermore, the S. sclerotiorum strain 1980 genome encodes 5 endo-polygalacturonases, 4 of which are expressed in culture or during infection (Li et al, 2004).…”
Section: Activity Of Enzymes Secreted By S Sclerotiorum During P Vusupporting
confidence: 68%
“…During infection of the P. vulgaris stem, the pattern of sspg expression was different from that observed in vitro: sspg1 and sspg3 were weakly expressed, sspg5 and sspg7 were highly expressed, and sspg6 displayed regulation during the later phases of infection (see Figure 5). We have previously reported similar observations (Oliveira et al, 2010). Furthermore, the S. sclerotiorum strain 1980 genome encodes 5 endo-polygalacturonases, 4 of which are expressed in culture or during infection (Li et al, 2004).…”
Section: Activity Of Enzymes Secreted By S Sclerotiorum During P Vusupporting
confidence: 68%
“…We have previously reported a variation in the expression pattern of Pvpgip genes (Pvpgip1, Pvpgip2, Pvpgip3, and Pvpgip4) following infection of common bean (P. vulgaris L. cv. BRS Pérola) hypocotyls with the necrotrophic fungal pathogen S. sclerotiorum (Oliveira et al, 2010). In this work, our results clearly show that the Pvpgip1, Pvpgip2, and Pvpgip3 transcript levels are strongly increased in plants treated with MeJA (observed in Fig.…”
Section: Polygalacturonase-inhibiting Proteins (Pgips)supporting
confidence: 55%
“…One possible explanation is that there is a lower pathogen level in the initial stage of infection and consequently a lower level of secreted PG. Another important factor is that in different stages of infection, S. sclerotiorum may induce the expression of different proportions of PG isozymes or different endoPG: exoPG ratios (Sella et al, 2005;Oliveira et al, 2010). EndoPGs are likely to exhibit variation in their susceptibility to PGIP, whereas exoPGs are likely to be unaffected (Cervone et al, 1990;Desiderio et al, 1997;Berger et al, 2000).…”
Section: Polygalacturonase (Pg) Activity and Inhibition Assaymentioning
confidence: 98%
“…This gene exhibited the highest relative expression level after inoculation in the present study. Oliveira et al (2010) also reported high PvPGIP2 expression in the Pérola bean cultivar, but only at 2 DAI, and there was a decrease in its expression from 3 DAI. Transgenic plants that express PvPGIP2 exhibit a reduction of about 35% in symptoms caused by Botrytis cinerea (Manfredini et al, 2005), and they exhibit reduced symptoms of Rhizoctonia solani, Phytophthora parasitica var.…”
Section: Discussionmentioning
confidence: 87%